Taliban narratives the use and power of stories in the Afghanistan conflict - Johnson, Thomas H.; DuPee, Matthew; Shaaker, Wali (New York, NY Oxford University Press, 2017)
"Why has the Taliban been so much more effective in presenting messages that resonate with the Afghan population than the United States, the Afghan Government and their allies? This book, based on years of field research and the assessment of hundreds of original source materials, examines the information operations and related narratives of Afghan insurgents, especially the Afghan Taliban, and investigates how the Taliban has won the information war. Taliban messaging, wrapped in the narrative of jihad, is both to the point and in tune with the target audiences it wishes to influence. On the other hand, the United States and its Kabul allies committed a basic messaging blunder, failing to present narratives that spoke to or, often, were even understood by their target audiences. Thomas Johnson systematically explains why the United States lost this 'battle of the story' in Afghanistan, and argues that this defeat may have lost the U.S. the entire war, despite its conventional and technological superiority."--Cover flap.
Introduction -- An overview of Taliban and other Afghan insurgent stories and an assessment of their master narratives -- Target audiences of Afghan narratives and stories -- Taliban and Afghan insurgent magazines, circulars, and newsletters -- The Taliban's use of Shabnamah (night letters) -- The Taliban's use of the Internet, social media video, radio stations, and graffiti -- The Afghans' and Taliban's use of poetry and Taranas -- The Layeha, the Taliban code of conduct -- Hezb-e-Islami Gulbuddin (HIG) propaganda activities --The United States' Afghan information and PSYOP campaign and a comparison with the Taliban's campaign -- Conclusions.
Includes bibliographical references (pages 299-364) and index.
English text with selection in Dari with parallel English translation from the Dari.
Keywords: Afghan War, 2001- -- Mass media and war; Mass media and war; Taliban members' writings